A abordagem behaviorista radical transmitida pelo livro de psicologia direcionado à formação de professores - Gioia, Paula Suzana (2001)
This study' s objective was to evaluate the information about behavior analysis/radical behaviorism presented in basic books utilized in education undergraduate courses in Brazil. Twenty-five Psychology books presented (a) at least two psychology approaches and (b) titles referred to education, learning or teaching were selected for analysis. The analysis of each book evaluated (a) the accuracy of the description of basic behavior concepts; (b) the accuracy of the description of radical behaviorism principles descriptions; (c) the occurrence of references to Skinner's work and (d) the description of Skinner' s views of teaching. Results indicated that accuracy of descriptions were not related to any kind of reference to Skinner's work. The majority of the Psychology text books analyzed were innacurate on their description of both, behavior analysis and radical behaviorism's principies When the text books presented accurate descriptions in a part of the text, most often the same subject was inaccurately presented in another part of the text, revealing inconsistency, probably because the authors' lack of familiarity to the behavior analysis. The majority of the concepts presented were related to the response-reinforcerment relations and extinction, while most of the radical behaviorism principles discussed were related to private events. Aversive control and its supposed relationship with totalitarianism is no longer presented; criticism and refusal behavior analysis/radical behaviorism are directed mainly to private events mainly. Radical behaviorism is still disqualified because it does not work with "mental" events. Skinnerian's views on teaching presented in the books are incomplete. They rely basically on descriptions of technical means of instruction. The importance of education for the culture is not discussed and the role of verbal behavior is not taken as the means of cultural transmission and new practices